Udayana University International Student Management: A Business Process Reengineering Approach - Pramartha, Cokorda Rai Adi; Mimba, Ni Putu Sri Harta (ComTech (Jakarta), 2020)
The research had two aims. First, it presented an overview and progress in understanding the current business process in the international program of Udayana University, which had a long queue for processing student admission documents. Second, it described how Business Process Reengineering (BPR) helped to improve the educational management services. Multiple interviews and a Forum Group Discussion (FGD) with the stakeholders were conducted. The reviews of the available documents, the current business process, and related complaint records were also carefully performed. The results show that the currently running batch processing system is a major challenge. The proposed solution reengineers the current business process and implements an information technology tool as a driver by digitizing the proposed solutions. The new business process leads to an improvement in processing the international student application from more than 60 days to only 29 days. Moreover, the proposed business process can minimize the opportunity loss of more than Rp3,8 billion annually.